Peroxisomal ATP-Binding Cassette Transporter COMATOSE and the Multifunctional Protein ABNORMAL INFLORESCENCE MERISTEM Are Required for the Production of Benzoylated Metabolites in Arabidopsis Seeds. Issue 1 (19th November 2013) - Bussell, John D.; Reichelt, Michael; Wiszniewski, Andrew A.G.; Gershenzon, Jonathan; Smith, Steven M.
Abstract : A peroxisomal substrate transporter and β-oxidation provide benzoic acid for the accumulation of benzoylated secondary metabolites during Arabidopsis seed development . Abstract: Secondary metabolites derived from benzoic acid (BA ) are of central importance in the interactions of plants with pests, pathogens, and symbionts and are potentially important in plant development. Peroxisomal β-oxidation has recently been shown to contribute to BA biosynthesis in plants, but not all of the enzymes involved have been defined. In this report, we demonstrate that the peroxisomal ATP-binding cassette transporter COMATOSE is required for the accumulation of benzoylated secondary metabolites in Arabidopsis ( Arabidopsis thaliana ) seeds, including benzoylated glucosinolates and substituted hydroxybenzoylcholines. The ABNORMAL INFLORESCENCE MERISTEM protein, one of two multifunctional proteins encoded by Arabidopsis, is essential for the accumulation of these compounds, and MULTIFUNCTIONAL PROTEIN2 contributes to the synthesis of substituted hydroxybenzoylcholines. Of the two major 3-ketoacyl coenzyme A thiolases, KAT2 plays the primary role in BA synthesis. Thus, BA biosynthesis in Arabidopsis employs the same core set of β-oxidation enzymes as in the synthesis of indole-3-acetic acid from indole-3-butyric acid.